2018
DOI: 10.7150/jca.26220
|View full text |Cite
|
Sign up to set email alerts
|

A Prognostic Nomogram for Cervical Cancer after Surgery from SEER Database

Abstract: Background: To develop and validate a nomogram based on the conventional measurements and log of odds between the number of positive lymph node and the number of negative lymph node (LODDS) in predicting prognosis for cervical cancer patients after surgery.Methods: A total of 8202 cervical cancer patients with pathologically confirmed between 2004 and 2014 were obtained from the Surveillance, Epidemiology, and End Results (SEER) database. All the patients were divided into training (n=3603) and validation (n=4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 25 publications
2
79
1
Order By: Relevance
“…However, other studies have reported inconsistent results. Wu et al [ 22 ] and Wang et al [ 23 ] reported an equivalent survival for patients with ADC and patients with SCC. In a retrospective competing-risks regression analysis of 2,108 patients with cervical cancer, Intaraphet et al [ 12 ] observed an association of ADC with poorer survival compared with SCC in advanced stages, while no difference was observed at early stages.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have reported inconsistent results. Wu et al [ 22 ] and Wang et al [ 23 ] reported an equivalent survival for patients with ADC and patients with SCC. In a retrospective competing-risks regression analysis of 2,108 patients with cervical cancer, Intaraphet et al [ 12 ] observed an association of ADC with poorer survival compared with SCC in advanced stages, while no difference was observed at early stages.…”
Section: Discussionmentioning
confidence: 99%
“…For a more accurate prognostic prediction, nomograms have been developed, and these nomograms show better performance than conventional staging systems in some cancers [51, 52]. In this study, we identified ARL3 as a prognostic marker for glioma, and constructed a nomogram and risk classification system.…”
Section: Discussionmentioning
confidence: 99%
“…a total of 4432 small-cell lung cancer patients were included in the study. We randomly divided these patient data into a training cohort of 1776 (40.07%) and a validation group of 2656 (59.93%) [6][7][8] with the createDataPartition function in R caret package.…”
Section: Data Sourcesmentioning
confidence: 99%